2022
DOI: 10.3390/cancers14235754
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Positive Gastroesophageal Cancers Are Associated with a Higher Risk of Brain Metastasis

Abstract: Brain metastasis from gastroesophageal adenocarcinomas (GOCs) is a rare but a devastating diagnosis. Human epidermal growth factor receptor 2 (HER2) is a prognostic and predictive biomarker in GOCs. The association of HER2 with GOC brain metastasis is not known. We performed a retrospective analysis of patients with GOCs with known HER2 status between January 2015 and November 2021. HER2 was assessed on either the primary tumour or metastasis by immunohistochemistry or in situ hybridization. The diagnosis of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(67 reference statements)
1
0
0
Order By: Relevance
“…The resulting median progression-free survival was 12 weeks. Previous studies found that HER2-positive GC patients had increased incidence of brain metastases [ 38 ], and similar results were also observed in HER2-positive breast cancer patients [ 39 ]. Several research groups have found that intrathecal trastuzumab was effective against HER2-positive leptomeningeal carcinomatosis for both GC and breast cancer patients [ 40 42 ].…”
Section: Discussionsupporting
confidence: 76%
“…The resulting median progression-free survival was 12 weeks. Previous studies found that HER2-positive GC patients had increased incidence of brain metastases [ 38 ], and similar results were also observed in HER2-positive breast cancer patients [ 39 ]. Several research groups have found that intrathecal trastuzumab was effective against HER2-positive leptomeningeal carcinomatosis for both GC and breast cancer patients [ 40 42 ].…”
Section: Discussionsupporting
confidence: 76%